DEVELOPING OF LEARNING MEDIA BASED ON STUDENT NEEDS FOR TENTH GRADE STUDENTS OF SMK NEGERI 2 TARAKAN - Aruji, Azlan B; Vega, Nofvia De; Haris, Abdul (Borneo Journal of English Language Education, 2022)
This research was aimed to develop learning media for class X at SMK Negeri 2 Tarakan and produce effective learning media products from the design and material aspects and attract students' interest by learning English. This research is a research and development of the ADDIE model which consists of five stages (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The instrument uses a material expert validation questionnaire, as well as a media validation (design) questionnaire and a student response questionnaire. The results of the research from the validation of interactive learning media through validation by material experts and media experts reached a percentage of 82% with very good qualifications and 78% with good qualifications. The results of the student response questionnaire to interactive learning media were divided into three, the one to one formative evaluation trial with a percentage of 71.2% with good qualifications, the small evaluation group test trial with a percentage of 78.2% with good qualifications, and the field test formative evaluation trial, with a percentage of 78.5% with good qualifications. Product trials were carried out in class X SMK Negeri 2 Tarakan. The results of research and development of learning media are suitable for use in learning English.